Population genomic analysis of the greater amberjack (Seriola dumerili) in the Mediterranean and the Northeast Atlantic, based on SNPs, microsatellites, and mitochondrial DNA sequences - Katirtzoglou, Aikaterini; Tsaparis, Dimitris; Kolios, Evangelos; Magoulas, Antonios; Mylonas, Constantinos C.; Fakriadis, Ioannis; Manousaki, Tereza; Tsigenopoulos, Costas S. (Frontiers in Fish Science, 2024)
The greater amberjack (Seriola dumerili) has attracted considerable economic interest since the 1990s because it possesses traits that distinguish it as a promising candidate in aquaculture. However, the challenges of its successful rearing, combined with the need to develop proper management practices, underline the importance of research into the genetic diversity of both wild and farmed stocks. We aimed to decipher the genetic structure of S. dumerili in the Eastern Mediterranean and the Northeast Atlantic using three types of genetic markers (mitochondrial control region sequences, microsatellites, and single nucleotide polymorphisms, or SNPs) to evaluate the population genetic structure of the species. The results were compared to those of previous studies of the species focusing on the Central Mediterranean and confirmed the presence of two divergent mtDNA haplogroups distributed without any detectable geographical structuring within the Mediterranean and the Atlantic. However, population analyses of the genetic structure of the species using either 10 microsatellites or a set of 1,051 SNP markers suggest that the species forms three genetically distinct groups, one in the Mediterranean and two in the Atlantic. The latter has so far not been reported in the Northeast Atlantic, and that this differentiation refers to samples from the Canary Islands is surprising. Fifteen candidate outlier SNP loci were identified in the data set, one located within the tead1a/TEF-1A gene, which has been associated with temperature acclimation of the medaka. This work enriches our knowledge of the genetic diversity of wild populations of the greater amberjack in the Mediterranean and the Northeast Atlantic and attempts to investigate signs of local adaptation toward a better understanding of the species distribution patterns. Future studies should be conducted to investigate the genomic regions associated with temperature acclimation in marine organisms that have to adapt to the ongoing climate change pressures, such as sea temperature rise, in order to survive.